T 1 EFFECT OF FEEDING TE ON THE GROWTH, FOOD CONVERSION PROTEIN EFFICIENCY OF SILVER DOLLAR, METYNNIS SCHREITMULLERI ( L), FRY - Singh, R. K.; Vartak, V. R.; Balange, A. K.; Chavan, J. B. (Journal of Indian Fisheries Association, 2015)
A 30-day experiment was conducted to determine the effects of varyingfeeding rates on the growth of fry of silver dollar, Metynnis schreitmulleri(Ahl). Silver dollar fry with an average initial body weight of 1.100 Â± 0.029gwere collected from a local fish breeder and fed a diet (35% protein and 6%fat) at the rate of 3, 6 and 9% of body weight per day in two equal meals. Percent weight gain increased from 54.54 to 118.18 with increased feeding rates,which were significantly different (p